Prevalence and Incidence of Medication-Treated Diabetes and Pattern of Glucose-Lowering Treatment During the COVID-19 Pandemic: Real-World Data from the Electronic Greek Prescription Database - Siafarikas, C.; Karamanakos, G.; Makrilakis, K.; Tsolakidis, A.; Mathioudakis, K.; Liatis, S. (Experimental and Clinical Endocrinology & Diabetes, 2024)
Objectives This study aimed to investigate the prevalence and incidence of medication-treated diabetes mellitus and the evolving patterns of glucose-lowering treatments the year before and during the first two years of the coronavirus disease 2019 (COVID-19) pandemic.Methods Data from the Greek electronic prescription database were analyzed for 2019, 2020, and 2021. The study population included individuals with active social security numbers. Prevalence and incidence rates were calculated based on the dispensing of glucose-lowering medications according to their unique anatomical therapeutic chemical (ATC) code.Results The study population comprised 10,289,140 individuals in 2019, 10,630,726 in 2020, and 11,246,136 in 2021. Diabetes prevalence rates were 8.06%, 6.89%, and 7.91%, and incidence rates were 16.8/1000, 8.6/1000, and 13.4/1000 individuals, respectively. Metformin was the most prescribed medication, and newer classes, like sodium-glucose cotransporter-2 inhibitors 2 (SGLT-2) inhibitors and glucagon like peptide-1 (GLP-1) receptor agonists exhibited increasing trends.Conclusions The study identified a decrease in medication-prescribed diabetes prevalence and incidence during the initial year of the COVID-19 pandemic, attributed to healthcare access restrictions. Subsequently, figures returned close to baseline levels. Glucose-lowering medication trends reflected adherence to local and international guidelines, with metformin as the cornerstone, and increasing preference for newer classes such as GLP-1 receptor agonists and SGLT-2 inhibitors.
Keywords: diabetes mellitus; prevalence; incidence; treatment; COVID-19 infection